Acute Inflammatory Optic Neuritis Associated with a Self-Taper of Oral Prednisone in a Patient Taking Adalimumab. (3rd May 2020) - Komandur, Abhinav; MacIntosh, Peter; Moss, Heather
ABSTRACT: Therapies, such as adalimumab, aimed at inhibiting the pro-inflammatory cytokine "tumour necrosis factor" (TNF) are effective and are frequently used in combination with non-biologic disease-modifying anti-rheumatic drugs to treat rheumatoid arthritis (RA) and other autoimmune diseases. Some reports indicate that, rarely, demyelinating CNS disorders such as optic neuritis can present in association with therapy initiation, whilst others suggest that there is no association between the two. Oral corticosteroids such as prednisone, though similarly effective in the treatment of inflammatory or auto-immune conditions, can be associated with adverse effects upon their discontinuation or tapering. We present a patient who developed an acute inflammatory optic neuropathy shortly after a self-taper of oral prednisone while being treated with adalimumab for RA, and discuss the challenge of deciding whether or not to halt anti-TNF therapy.